KAJIAN PENATAAN ADMINISTRASI PEMERINTAHAN DESA BALAI MAKAM KECAMATAN MANDAU KABUPATEN BENGKALIS - aini, Mar’ (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
The Study of administrative structuring of Village Government aims to find the things that need tobe addressed about the administration, especially administrative administration related to thesmooth administrative process of both General Administration, Population Administration,Finance Administration, Development Administration and other administration related to theactivities of Village Consultative Agency as well as those related to the activities of otherCommunity Institutions in Balai Makam village, Mandau Sub-district, Bengkalis District, and theadministration of the Government concerning the strengthening of the Village Institution, thedelegation of authority to the village and the Village Allocation Fund.The results of the administrative study concerning public administration in general are quite goodwith the availability of complete administrative books although there are some things that need tobe addressed regarding the procedures, records and archiving as authentic documents and proofsfor the benefit of development, regulation and quick service to the community . For that the thingsthat must be done, among others, complement the facilities and infrastructure required for theactivities of Administration of the business, the guidance of the village head against the villageapparatus about the procedures and the implementation of administrative activities according totheir respective duties and functions. As for the implementation of village governance concerningthe strengthening of the Village Institution is good with the functioning of the VillagePermusyaratan Board as a partner of the Village Government, but there are things to note in orderto carry out their duties in accordance with existing procedures and laws and regulations, bothnational, preferably in the filling of institutional positions, the village selectively conductsrecruitment by selecting persons with capabilities and relevant to the village governance issue.Keywords: Administrative Structuring, Village Government